2005
DOI: 10.1038/nm1301
|View full text |Cite
|
Sign up to set email alerts
|

NKCC1 transporter facilitates seizures in the developing brain

Abstract: During development, activation of Cl(-)-permeable GABA(A) receptors (GABA(A)-R) excites neurons as a result of elevated intracellular Cl(-) levels and a depolarized Cl(-) equilibrium potential (E(Cl)). GABA becomes inhibitory as net outward neuronal transport of Cl(-) develops in a caudal-rostral progression. In line with this caudal-rostral developmental pattern, GABAergic anticonvulsant compounds inhibit motor manifestations of neonatal seizures but not cortical seizure activity. The Na(+)-K(+)-2Cl(-) cotran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

60
942
4
11

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 873 publications
(1,017 citation statements)
references
References 49 publications
60
942
4
11
Order By: Relevance
“…Second, [Cl − ] i accumulation is caused (at least in immature neurons) by the activation of NKCC1 cotransporter that imports Na + , K + , and Cl − (Achilles et al, 2007;Sipilä et al, 2009). As discussed in Section 9, this mechanism may play an important role in neonatal seizures (Dzhala et al, 2005(Dzhala et al, , 2010Nardou et al, 2009). Third, GABA A receptormediated depolarizations are contributed by HCO 3 − currents that have quite positive reversal potentials (−10 to −15 mV) (Staley et al, 1995;Lamsa and Kaila, 1997;Kaila et al, 1993Kaila et al, , 1997Rivera et al, 2005).…”
Section: Gaba a Receptor-mediated Depolarizing Actionsmentioning
confidence: 98%
“…Second, [Cl − ] i accumulation is caused (at least in immature neurons) by the activation of NKCC1 cotransporter that imports Na + , K + , and Cl − (Achilles et al, 2007;Sipilä et al, 2009). As discussed in Section 9, this mechanism may play an important role in neonatal seizures (Dzhala et al, 2005(Dzhala et al, , 2010Nardou et al, 2009). Third, GABA A receptormediated depolarizations are contributed by HCO 3 − currents that have quite positive reversal potentials (−10 to −15 mV) (Staley et al, 1995;Lamsa and Kaila, 1997;Kaila et al, 1993Kaila et al, , 1997Rivera et al, 2005).…”
Section: Gaba a Receptor-mediated Depolarizing Actionsmentioning
confidence: 98%
“…However, caution is warranted as work from our lab has also shown that 17β-estradiol may exacerbate developmental injuries with underlying GABA A receptor involvement. These include fetal alcohol syndrome and seizures (Dzhala et al, 2005;Galindo et al, 2005;Khalilov et al, 2005;Young et al, 2005). While 17β-estradiol exerts substantial neuroprotection from hypoxia/ischemia, the benefit it confers may be dependent upon the type of injury and the age of the infant.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, during the very early stages of development (prenatal-early neonatal), Cl -flow is regulated by the inward NKCC1, which increases concentrations of intracellular Cl - [121]. As a result, during early stages of development, the GABA-A receptor-mediated opening of Cl -channels leads to an outward Cl -flow and, thus, to excitation [122]. One of the presumed consequences of GABA acting as an excitatory neurotransmitter early in life is the ineffectiveness of GABAergic antiepileptic drugs [122,123] on the one hand, and the antiepileptic effects of NKCC1 blockers on the other hand.…”
Section: Rapid Kindling: a Model Of Epileptogenesis In The Developingmentioning
confidence: 99%
“…As a result, during early stages of development, the GABA-A receptor-mediated opening of Cl -channels leads to an outward Cl -flow and, thus, to excitation [122]. One of the presumed consequences of GABA acting as an excitatory neurotransmitter early in life is the ineffectiveness of GABAergic antiepileptic drugs [122,123] on the one hand, and the antiepileptic effects of NKCC1 blockers on the other hand. Indeed, the NKCC1 blocker bumetanide exerted acute anticonvulsant effects in immature animals [123].…”
Section: Rapid Kindling: a Model Of Epileptogenesis In The Developingmentioning
confidence: 99%